LANGUAGE ATTITUDES AND LANGUAGE CHOICE AMONG STUDENTS IN YOGYAKARTA: A CASE STUDY AT UNIVERSITAS SANATA DHARMA - Fitriati, Anna; Wardani, Maria Magdalena Sinta (International Journal of Humanity Studies (IJHS), 2020)
Yogyakarta is a multicultural city in which people from different regions and ethnicity live and well known as one of the best foreign tourist destinations in Indonesia. This situation gives an excellent opportunity for the community to communicate with others whose different cultural backgrounds, ethnicity, and language. Commonly, they talk in Javanese, the local language spoken in Yogyakarta. Meanwhile, due to the engagement with those who speak in different languages, Indonesian and English are gaining more frequent usage. Concerning this situation, this paper is to investigate the language choice among students in Yogyakarta. This study also scrutinises their language attitude toward English, colloquial Indonesian, and local languages. In achieving the objectives, a sociolinguistic questionnaire is given to 100 sample respondents who are the students of Universitas Sanata Dharma. The results show that the students have appreciative attitudes towards the colloquial Indonesian, English, and local languages. The investigation on the language choice indicates that the students choose to communicate using Indonesian. The dominance of Indonesian shifts the use of local languages.Â